Chemoprevention Gene Therapy (CGT): Novel Combinatorial Approach for Preventing and Treating Pancreatic Cancer - Sarkar, S.; M. Azab, B.; K. Das, S.; A. Quinn, B.; Shen, X.; Dash, R.; Emdad, L.; Thomas, S.; Dasgupta, S.; Su, Z.-Z.; Wang, X.-Y.; Sarkar, D.; et al. (Current Molecular Medicine, 2013)
Pancreatic cancer remains one of the deadliest of all cancers despite aggressive surgical treatment combined with adjuvant radiotherapy and chemotherapy. Chemoresistance and radioresistance are the principal causes of failure of pancreatic cancer patients to respond to therapy. Conditionally replicationcompetent adenovirus (CRCA)-based cancer gene therapy is an innovative strategy for treating cancers displaying inherent resistance to treatment. Limitations of current adenovirus (Ad)-based gene therapies for malignant tumors include lack of cancer-specificity, and effective and targeted delivery. To remedy this situation, CRCAs have been designed that express E1A, necessary for Ad replication, under the control of a cancer-specific progression elevated gene-3 promoter (PEG-Prom) with concomitant expression of an immunomodulatory cytokine, such as mda-7/IL-24 or interferon-γ (IFN-γ), under the control of a ubiquitous and strong cytomegalovirus promoter (CMV-Prom) from the E3 region. These bipartite CRCAs, when armed with a transgene, are called cancer terminator viruses (CTVs), i.e., Ad.PEG-E1A-CMV-mda-7 (CTV-M7) and Ad.PEG-E1A-CMV-IFN-γ (CTV-γ), because of their universal effectiveness in cancer treatment irrespective of p53/pRb/p16 or other genetic alterations in tumor cells. In addition to their selective oncolytic effects in tumor cells, the potent ‘bystander antitumor’ properties of MDA-7/IL-24 and IFN-γ embody the CTVs with expanded treatment properties for both primary and distant cancers. Pancreatic cancer cells display a “translational block” of mda-7/IL-24 mRNA, limiting production of MDA-7/IL-24 protein and cancer-specific apoptosis. Specific chemopreventive agents abrogate this “translational block” resulting in pancreatic cancer-specific killing. This novel chemoprevention gene therapy (CGT) strategy holds promise for both prevention and treatment of pancreatic cancers where all other strategies have proven ineffective.
Keywords: chemoprevention